2000
DOI: 10.1177/021849230000800409
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis Size in Aortic Valve Replacement: Surgeon-Related Variable

Abstract: A retrospective analysis was performed to determine the surgeon's impact on the selection of the size of prosthesis in aortic valve replacement. From January 1993 through December 1997, 748 patients underwent either isolated aortic valve replacement (530) or double valve replacement (218) with bileaflet valves. Depending on the operating surgeon, patients were divided into group A (367) or group B (381). Preoperative, intraoperative, and postoperative variables in both groups were compared. Groups A and B were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In contrast, 80% of our patients receieved valves 23 mm or larger in size. Aortic valve dimension in the Indian population is similar to that in the West 23,24 Observations of aortic root dimensions in cadavers in India has shown that the mean aortic annulus diameter in adult Indian males aged 16-60 years is 23.2±1.9 mm and in the adult Indian females aged 16-65 years is 21.2±2.5 mm which corresponds to valve areas of 4.2 cm 2 (range 3.6-4.9 cm 2 ) and 3.5 cm 2 (range 2.8-4.4 cm 2 ) respectively 24 . Therefore valve prosthesis of 25-31 mm diameter are considered to match the native valves in terms of area 24 .…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In contrast, 80% of our patients receieved valves 23 mm or larger in size. Aortic valve dimension in the Indian population is similar to that in the West 23,24 Observations of aortic root dimensions in cadavers in India has shown that the mean aortic annulus diameter in adult Indian males aged 16-60 years is 23.2±1.9 mm and in the adult Indian females aged 16-65 years is 21.2±2.5 mm which corresponds to valve areas of 4.2 cm 2 (range 3.6-4.9 cm 2 ) and 3.5 cm 2 (range 2.8-4.4 cm 2 ) respectively 24 . Therefore valve prosthesis of 25-31 mm diameter are considered to match the native valves in terms of area 24 .…”
Section: Discussionmentioning
confidence: 67%
“…Though implantation of small prosthesis may result in significant symptomatic relief, this may produce patient-prosthesis mismatch with resultant transvalvuar gradients at rest which are increased during exercise 19 . Large size valves have favourable hemodynamics and low gradients with resultant good exercise performance 24 . Valve size is therefore a significant determinant of postoperative exercise capacity 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also published our observation on the surgeon as a variable for implantation of a larger prosthesis. 9 It was clear from this study that the actual size of prosthesis implanted was primarily determined by the surgeon and not always by the measured aortic annulus diameter.…”
mentioning
confidence: 86%